INFLUENCE OF ADJUVANTS ON THE SURFACE TENSION, DEPOSITION AND EFFECTIVENESS OF HERBICIDES ON FLEABANE PLANTS - Castro, E. B. [UNESP]; Carbonari, C. A. [UNESP]; Velini, E. D. [UNESP]; Gomes, G. L. G. C. [UNESP]; Belapart, D. [UNESP] (Univ Federal Vicosa, 2018)
The use of herbicides is widespread in weed management, and adjuvants are added to the spray solution to improve the effectiveness of applications. The goal was to evaluate the influence of adjuvants added to the herbicides saflufenacil and glyphosate, isolated or in combination, and the effects on the surface tension, deposition and effectiveness in post-emergence applications to control Conyza sumatrensis. Experiments were conducted completely randomized experimental design to evaluate surface tension (TS), deposition and herbicide effectiveness. The treatments were glyphosate, glyphosate + saflufenacil and saflufenacil with or without the adjuvants Natur'al oleo (R), Assist (R), Aterbane (R), Sillwet L-77 and Dash HC (R) (surface tension). For the experiments about mixture deposition and herbicide effectiveness, the factorial scheme 3 x 5 was adopted in the experiment performed in April, where factor A corresponded to the combination of the herbicieds glyphosate, saflufenacil and glyphosate + saflufenacil, and factor B was the addition of the adjuvants Natur'al oleo (R), Assist (R), Aterbane (R), Sillwet L-77. For experiments conducted in November, the adjuvant Dash HC (R) was added, and the 3x6 factorial design was adopted. The adjuvants reduced the ST of the herbicide mixture, and Silwet L-77 (R) was the most effective one. However, the ST reduction did not influence the mixture deposition on C. sumatrensis plants. The use of adjuvants did not result in an effective control for the applications with sole glyphosate.
Keywords: Conyza sumatrensis; glyphosate; saflufenacil; surfactants